RAINBOW FISH MARKETING TRAINING: BUSINESS OPPORTUNITIES OF RAINBOW FISH CULTIVATION FARMING DURING A PANDEMIC ERA (COMMUNITY SERVICE OF FISHERIES MANAGEMENT MASTER PROGRAM OF UNIVERSITAS TERBUKA) - Puspitasari Sudarmo, Agnes; Panggabean, Donwill; Sujono, Sujono; Lestari Sapuriningsih, Chikita; Munawir, Abdillah (LPPM Univ. Ibn Khaldun Bogor, 2023)
During this pandemic, many businesses collapsed and were unable to get back up, especially in the micro-economy and MSME sectors. MSMEs during this pandemic need to be assisted through mentoring and training to strengthen their businesses, so that they are able to deal with the current situation well. The purpose of this community service is to improve and develop the ornamental fish fishery business for MSMEs and groups of ornamental fish farmers in the Ciseeng District by providing intensive assistance and training on how to cultivate ornamental fish properly at the business location, namely in Ciseeng District, Bogor Regency. The type of ornamental fish being developed is the type of rainbow boesemani (Melanotaenia boesemani) originating from Papua or people generally know it by the name rainbow fish. This community service activity was carried out in Ciseeng District by involving Open University students, ornamental fish entrepreneurs in Ciseeng and Mount Sindur Districts. It is hoped that with this community service activity and assistance to these ornamental fish actors, they will be able to overcome the constraints of limited business capital and obstacles in obtaining broodstock and be able to apply good and correct methods of cultivating ornamental fish supported by appropriate marketing methods so that these MSME businesses can be more empowered.